My Parents Won't Stop Talking! - Hunsinger, Emma; Walden, Tillie, 1996- (New York : Roaring Brook Press, 2022)
A little girl has big plans for her day at the park, but when her two Mums stop to talk to some chatty neighbors she is convinced that her whole day will be completely ruined.
Ages 3-6.
Grades K-1.
Keywords: Mother and child -- Juvenile fiction; Patience -- Juvenile fiction; Neighbors -- Juvenile fiction; Patience -- Fiction; Mother and child -- Fiction; Neighbors -- Fiction